Automation Testing Api, Android, dan Website Menggunakan Serenity Bdd Pada Software Sistem Manajemen Rumah Sakit - Bagas Dwi Saputra; Arnisa Stefanie (Jurnal Ilmiah Wahana Pendidikan, 2023)
System testing has an important part to produce a product with high quality and time saving. Manual testing has many drawbacks compared to automated testing. This research discusses automation testing. Automation testing will greatly help quality application developers and time efficiency. Script automation testing based on cucumber serenity running behind the scenes using jenkis. Test scenario system, running with the Java programming language. Test conclusions drawn from testing automatically generate testing reports from the scenarios that have been made. Testing can be seen more easily in the form of an idex website compared to manual testing.